Bahasa dan Kekuasaan dalam Historiografi Islam Marshall G.S. Hodgson - Greg Soetomo (ISLAM NUSANTARA:Journal for the Study of Islamic History and Culture, 2021)
Historian has been preserving a historical unity and continuity as a truth. There is an assumption that history has a ‘constant’. This paper explains and proves otherwise. This writing understands history is in fact filled with various ruptures, differences, and deviations. This uncertainty has taken place when ‘language’ becomes a focus of the study of history. In his L’Archeologie du savoir (1969), Michel Foucault (1926-1984) rejected the preconception of history as unity and continuity. He believed the history as a journey with various ruptures, differences, and irregularities that reveal uncertainty. This reversal has taken place when language as the focus’ study in the history of knowledge. Foucault has called this method as the Archaeology of Knowledge. This is the question which this paper is going to respond: “How does Michel Foucault’s archaeology of knowledge, the analytical philosophy of language, elucidate the diversity within Marshall G.S. Hodgson’s history of Islam?” These three below mentioned questions respectively reflect a three-fold dimension of the diversity in Foucault’s thoughts as explained in his L’Archeologie du savoir (poststructuralism-structuralism, postmodernism, and philosophy of history). First, how does Hodgson, as a structuralist, write the history of Islam by way of developing system of discourses to reveal meaning; at the same time, as a poststructuralist, he reveals incoherence of discourses and its plurality of meanings? Second, how do we understand that the social structure in the history cannot be simply detached from the chains of power as a constitutive dimension of discourse? Third, how do we comprehend, that in every stages of history, they have its distinctive episteme and diversity of thoughts that support the formation of discourses? This research is essentially to explain the three perspectives of Foucault’s philosophy. At the same time, the three approaches in Hodgson’s writing on the history of Islam are also being explored. Both points of convergence and of divergence have become the whole study of this paper.